Kajian Tentang Bencana Dan Dampak Gempa Bumi di Cianjur Bersama Mahasiswa Teknik Sipil Nusaputra - Danang Purwanto; Dio Damas Permadi; Utamy Sukmayu Saputri; Umar Aditiawarman; Dini Oktarina Dwi Handayani; Deshinta Arovva Dewi (Jurnal Abdi Nusa, 2023)
This routine study is an activity that aims to increase knowledge and understanding of a problem or event and aims to find new solutions or innovations in solving it. Lack of interest in literacy and a sense of concern for students towards local and national problems or issues, therefore Therefore, this routine study is always carried out once a month with the aim of developing critical thinking, reasoning, students' sense of concern for problems in the local and national areas and finding solutions to issues that exist in the wider community. The occurrence of an earthquake in Cianjur had a major impact in various fields. Especially in a building structure that suffered a lot of damage.